Uses of HDFS in Metadata Management System - Durga, N; Ragupathi, D; Raj Kumar, V (International Journal of Computer Sciences and Engineering, 2014)
A (HDFS) Hadoop Distributed File System is intended to store very large data sets unfailingly and to stream those data sets at elevated bandwidth to consumer applications. Metadata managing is serious to distributed file system. In HDFS design, a solo master server administers all metadata, while numerals of data servers pile up file data. This design can’t gather the exponentially improved storage claim in cloud computing, as the solo master server may happen to a performance traffic jam. Proportional study of a metadata managing proposal is done. Its consist of three techniques tree separation, hashing and reliable hashing of metadata managing proposal. Out of these three proposals reliable hashing is the best techniques which utilize multiple Name Nodes, and segregate the metadata into “Buckets” which can be energetically move around among Name Nodes according to system job weight. To uphold consistency, metadata is simulated in dissimilar Name Nodes with log duplication knowledge, and Paxos algorithm is adopted to keep duplication uniformity.